1997
DOI: 10.1085/jgp.109.5.647
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Voltage Dependence and Ca2+ Regulation of mslo Large Conductance Ca-activated K+ Channels

Abstract: The kinetic and steady-state properties of macroscopic mslo Ca-activated K+ currents were studied in excised patches from Xenopus oocytes. In response to voltage steps, the timecourse of both activation and deactivation, but for a brief delay in activation, could be approximated by a single exponential function over a wide range of voltages and internal Ca2+ concentrations ([Ca]i). Activation rates increased with voltage and with [Ca]i, and approached saturation at high [Ca]i. Deactivation rates generally decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

57
360
2
10

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 266 publications
(429 citation statements)
references
References 78 publications
(181 reference statements)
57
360
2
10
Order By: Relevance
“…6A,B). Similar to previous reports (Cui et al, 1997), the increase in [Ca 2ϩ ] i resulted in a decreased time constant for channel activation (Fig. 6A).…”
Section: Kcnq Channels Control the Resting Submembrane [Ca 2؉ ] In Cosupporting
confidence: 91%
See 2 more Smart Citations
“…6A,B). Similar to previous reports (Cui et al, 1997), the increase in [Ca 2ϩ ] i resulted in a decreased time constant for channel activation (Fig. 6A).…”
Section: Kcnq Channels Control the Resting Submembrane [Ca 2؉ ] In Cosupporting
confidence: 91%
“…these channels, however, was activated when V R was shifted to depolarized potentials as a result of block of the KCNQ4 channels. Activation of BK channels at potentials as negative as Ϫ65 mV is thought to require [Ca 2ϩ ] i in the upper micromolar range (Adelman et al, 1992;Cui et al, 1997), suggesting that the linopirdine-induced depolarization led to a voltage-dependent increase in [Ca 2ϩ ] i , most likely arising from the activation of voltage-gated Ca 2ϩ channels (Ca V ). Consistent with this idea, a hallmark of IHC Ca 2ϩ channels (␣1D L-type Ca 2ϩ channels, Ca V 1.3) is their unusually negative activation range (Platzer et al, 2000;Xu and Lipscombe, 2001).…”
Section: Kcnq Channels Control the Resting Submembrane [Ca 2؉ ] In Comentioning
confidence: 99%
See 1 more Smart Citation
“…4C. This type of plot was extensively used in the characterization of BK channels and gave the first hint of the existence of a low affinity Ca 2+ site (Wei et al, 1994;Cui et al, 1997). Fig.…”
Section: Sensing Elementsmentioning
confidence: 99%
“…It would be interesting to test for the possibility that the low Ca 2+ affinity of these putative Ca 2+ and Mg 2+ sites is determined by the close proximity of the histidine residues. Despite the fact that it contains an S4 domain, the molecular nature of the BK channel voltage-dependence remained unclear until it was unequivocally demonstrated that depolarizing voltages are able to activate the BK channel in the absence of Ca 2+ (Pallota, 1985;Meera et al, 1996;Cui et al, 1997;Cox et al, 1997;Stefani et al, 1997;Rothberg and Magleby, 2000;Nimigean and Magleby, 2000;Taludker and Aldrich, 2000). One of the first observations in support of the presence of an integral voltage sensor in the BK channel-forming protein is depicted in Figure 4B.…”
Section: Sensing Elementsmentioning
confidence: 99%